Statistical techniques in business & economics - Lind, Douglas A. (McGraw-Hill/Irwin, 2008)
The book delivers clear and understandable explanations of essential business statistics concepts. Along with the text, this edition offers a wide range of supplements that bring greater clarity to statistical concepts while also giving you the flexibility of additional coursework.